2018
DOI: 10.3390/polym10060601
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Performances of Phase Change Microcapsules with a Polymer/Diatomite Hybrid Shell for Thermal Energy Storage

Abstract: The mechanical behavior of phase-change microcapsules (microPCMs) is of vital significance for practical applications in thermal energy storage. Hence, a new type of microPCMs based on an n-octadecane (C18) core and a melamine-urea-formaldehyde (MUF)/diatomite hybrid shell was developed through in situ polymerization. Based on SEM micrographs, most microPCMs exhibited a nearly spherical and smooth microstructure, with broadened particle size distributions. It was confirmed by Fourier transform infrared (FTIR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The phase change characteristics of PCM, MPCM, CMPCM1 and CMPCM2, as shown in Fig. 6 a,b, indicated that the change in the melting points could be attributed to motion of the PCM inside a confined space and an increase in the heat transfer surface area 42 . The difference in the latent heat capacities of microcapsules can be due to the lower shell strength, allowing some quantity of PCM to leak out of shell materials for MPCM and CMPCM1 43 .…”
Section: Discussionmentioning
confidence: 95%
“…The phase change characteristics of PCM, MPCM, CMPCM1 and CMPCM2, as shown in Fig. 6 a,b, indicated that the change in the melting points could be attributed to motion of the PCM inside a confined space and an increase in the heat transfer surface area 42 . The difference in the latent heat capacities of microcapsules can be due to the lower shell strength, allowing some quantity of PCM to leak out of shell materials for MPCM and CMPCM1 43 .…”
Section: Discussionmentioning
confidence: 95%
“…MUF presents a broad and intense absorption peak around 3350 cm −1 , which is attributed to the superimposition of N-H and O-H bond stretching vibrations. The characteristic peak near 1338 cm −1 is due to the C-N stretching vibrations, and the peak at 812 cm −1 reflects the characteristic peak of the triazine ring vibrations, which are all typical vibrations of MUF resins functionalities [23]. SG shows a strong and broad absorption peak at 3405 cm −1 , which corresponds to the stretching vibration of -OH, while the peaks at 1718 cm −1 and 1620 cm −1 correspond to the stretching vibration of C=O and C=C, respectively [41].…”
Section: Chemical Composition Of Mcpcmmentioning
confidence: 99%
“…Incorporating inorganic functional particles into the organic shell can effectively address the weaknesses of organic shell materials and synergistically enhance both thermal conductivity and mechanical strength [11]. Sun et al [23] successfully prepared MCPCM by employing sodium dodecyl sulfate as the emulsifier, n-octadecane as the core material, and MUF and diatomaceous earth as the hybrid shell components. The results of this study show that the incorporation of diatomaceous earth enhances the mechanical strength of MCPCM.…”
Section: Introductionmentioning
confidence: 99%
“…Diatomite soil has special structural and chemical stability, which is characterized by soft texture, high adsorption, high porosity, and low density [3]. At present, it is often used as an adsorption material in the chemical industry [4][5][6]. The main component of diatomite soil is SiO 2 , and it contains more clay minerals, detritus, and organic matter [7][8][9].…”
Section: Introductionmentioning
confidence: 99%